Mobile ground-based measurements of aerosol and trace gases during a prescribed burning experiment in boreal forest in Finland - Pirjola, Liisa; Virkkula, Aki; Petäjä, Tuukka; Levula, Janne; Kukkonen, Jaakko; Kulmala, Markku (Finnish Environment Institute, 2016)
Peer reviewed